Lymphocyte Scattergram Profile in the Elderly With Bone Pain and Anemia - Hayati, Taureni; Prihatn, Delita; Tristina, Nina (Green Publisher Indonesia, 2022)
Old age according to the World Health Organization in 2017, is someone who has entered the age of 60 years and over. Due to various aging processes that occur in the elderly, the elderly will experience many complaints, one of which is bone pain and anemia. Various conditions in the elderly can cause bone pain and anemia, including: osteoporosis, osteomalacia, renal osteodystrophy, osteonecrosis, malignancy or bone metastases. From these conditions, a lymphocyte profile can be seen using a white blood cell differential scattergram in areas A, B, C, D, and E, according to the purpose of the study, wanted to know the scattergram profile of lymphocytes in the elderly with bone pain and anemia. This research method uses descriptive observation with a cross-sectional design method. The study was conducted from February-June 2020. The research subjects were elderly patients who experienced bone pain and anemia. Bone pain was measured by the Numeric Rating Scale on a scale of 1-10. Anemia was measured by examining hemoglobin on a hematology analyzer, then scattergram analysis was carried out through WDF using Sysmex XN 1000. The results of this study showed that the scattergram profile of lymphocytes in most elderly subjects with bone pain and anemia was in the SSC (A2, A3), SFL area. (B2, C2, D3, E3), which means that there are many changes in the lymphocyte profile, more atypical lymphocyte cells and suspicion of abnormal plasma cells or lymphocyte cells.